Bulk and single-cell transcriptome profiling reveals the dynamic immune response in granulomatous amebic encephalitis caused by Balamuthia mandrillaris: a cohort study - Zhang, Jingjia; Jia, Xinmiao; Yang, Bin; Ge, Ying; Jiang, Wei; Cong, Yang; Wu, Huanwen; Liu, Huifang; Tian, Jingjing; Xu, Yingchun; Yang, Qiwen (Frontiers in Immunology, 2025)
IntroductionBalamuthia mandrillaris infection in humans is rare and usually fatal. It is well established that B. mandrillaris can cause granulomatous amebic encephalitis (GAE). However, little is known about the factors that determine B. mandrillaris pathogenicity and its host-specific interactions.MethodsIn this study, we conducted a cohort study of five patients with B. mandrillaris GAE and analyzed immune pathway alterations, differentially expressed genes (DEGs), and changes in immune cell composition to delineate the immune response in this rare infectious disease using bulk transcriptome analysis. Notably, we conducted bulk and single-cell transcriptome sequencing on paired cerebrospinal fluid (CSF) and blood samples from a single patient across three distinct stages of infection.ResultsAnalysis of seven CSF specimens revealed a total of 5,177 DEGs as the infection progressed. The most enriched pathway among the upregulated DEGs was the “PI3K-Akt signaling pathway”. Moreover, its upstream pathways, the “Toll-like receptor (TLR) signaling pathway” and “JAK/STAT signaling pathway”, were also upregulated. Among these, TLR2, TLR9, and IFN-I/III-related genes played a crucial role in activating these pathways. The single-cell transcriptome results served to validate these findings.DisscusionOverall, our study aimed to elucidate the pathogenic mechanisms underlying B. mandrillaris GAE, providing novel insights into the associated immune responses.